2023
DOI: 10.9734/jammr/2023/v35i115026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Prevalence of Syphilis among Pregnant Women and Prospective Blood Donors in Ekiti State, South Western Nigeria

Abstract: Background: Syphilis is a highly contagious, systemic bacterial illness that poses a serious public health threat on a worldwide scale. In addition to being spread sexually, the illness can also be contracted through blood donation. To accurately evaluate the epidemiological pattern and community impact of the disease, this research sought to ascertain the seroprevalence of syphilis among pregnant women and potential blood donors. In Ekiti State, southwest Nigeria, a comparative study was conducted to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Additionally, it increases the risk of early death in an additional 215,000 infants 19 . In Africa, syphilis infection rates among women of reproductive age range from 0.36% to 3.6%, whereas blood donors have recorded rates ranging from 0.71% to 20% 20 . A study conducted in Ghana revealed a prevalence rate of 0.3% among pregnant women and 3.7% among healthy blood donors) 21 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it increases the risk of early death in an additional 215,000 infants 19 . In Africa, syphilis infection rates among women of reproductive age range from 0.36% to 3.6%, whereas blood donors have recorded rates ranging from 0.71% to 20% 20 . A study conducted in Ghana revealed a prevalence rate of 0.3% among pregnant women and 3.7% among healthy blood donors) 21 …”
Section: Introductionmentioning
confidence: 99%